1999
DOI: 10.1097/00001756-199909090-00004
|View full text |Cite
|
Sign up to set email alerts
|

Decreased brain infarct following focal ischemia in mice lacking the transcription factor E2F1

Abstract: E2F1+/- mice subjected to 2 h middle cerebral artery occlusion developed an infarct of 77.0 +/- 3.2 mm3 (mean +/- s.e.m., n = 15) in the ischemic hemisphere after 24 h reperfusion. A significantly smaller infarct of 58.8 +/- 4.8 mm3 (n = 15; p < 0.01) was found in E2F1-/- animals. Both deficient and normal mice had similar cerebral angioarchitecture and intra-ischemic decreases in regional blood flow. Similar areas of hypoxia in both groups of ischemic animals were demonstrated directly by immunohistochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 4 publications
5
43
0
Order By: Relevance
“…Because E2F-1 is known to regulate its own transcription, this result is consistent with the notion of deregulated activation of E2F-1 complexes during death induced by low K ϩ ; a concept suggested by previous reports demonstrating both Rb phosphorylation and loss in this same death paradigm (17). Our findings of significant neuroprotection as a result of E2F-1 deficiency are also consistent with the in vivo observations of others showing that E2F-1 deficiency is partially protective against death induced by Rb deficiency (46) and ischemia (59). In addition, we have also recently shown that E2F-1 deficiency is protective against ␤-amyloid toxicity (60).…”
Section: E2f-1 Expression Evokes Caspase Activation and Death In Asupporting
confidence: 93%
“…Because E2F-1 is known to regulate its own transcription, this result is consistent with the notion of deregulated activation of E2F-1 complexes during death induced by low K ϩ ; a concept suggested by previous reports demonstrating both Rb phosphorylation and loss in this same death paradigm (17). Our findings of significant neuroprotection as a result of E2F-1 deficiency are also consistent with the in vivo observations of others showing that E2F-1 deficiency is partially protective against death induced by Rb deficiency (46) and ischemia (59). In addition, we have also recently shown that E2F-1 deficiency is protective against ␤-amyloid toxicity (60).…”
Section: E2f-1 Expression Evokes Caspase Activation and Death In Asupporting
confidence: 93%
“…In addition, E2F1 expression is sufficient to promote the death of proliferating cells (39). Finally, E2F1-deficient mice are resistant to the death of cultured cortical and cerebellar granule neurons evoked by ␤-amyloid toxicity and low extracellular K ϩ , respectively (12) (M. O'Hare and D.S.P., unpublished data), and to ischemic damage (40). However, in these cases, protection is transient and͞or incomplete, suggesting the participation of additional, complementary death pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it may function to promote the senescent state and may participate in neuronal apoptosis. E2F1 is known to have an important role in driving apoptosis in several cell types, including neurons (Giovanni et al, 2000;MacManus et al, 1999;Park et al, 2000). However, recent studies have shown that E2F2 can also exhibit pro-apoptotic activity (Dirks et al, 1998).…”
Section: Discussionmentioning
confidence: 99%